2008
DOI: 10.1134/s0202289308010118
|View full text |Cite
|
Sign up to set email alerts
|

Ray optics in the field of a nonminimal Dirac monopole

Abstract: Based on the analogy with non-minimal SU (2) symmetric Wu-Yang monopole with regular metric, the solution describing a non-minimal U (1) symmetric Dirac monopole is obtained. In order to take into account the curvature coupling of gravitational and electromagnetic fields, we reconstruct the effective metrics of two types: the so-called associated and optical metrics. The optical metrics display explicitly that the effect of birefringence induced by curvature takes place in the vicinity of the non-minimal Dirac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 20 publications
(34 reference statements)
0
42
0
1
Order By: Relevance
“…One attempt to realize this idea was made in [7], where the approach based on the symmetry of the susceptibility tensor R ikmn (3) is proposed. In [8,9,13,18] special sets of coupling parameters were found, for which the metric functions of non-minimally coupled systems happened to be regular, and the absence of singularity became one of the arguments for the non-minimal extension of the Einstein-Maxwell theory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One attempt to realize this idea was made in [7], where the approach based on the symmetry of the susceptibility tensor R ikmn (3) is proposed. In [8,9,13,18] special sets of coupling parameters were found, for which the metric functions of non-minimally coupled systems happened to be regular, and the absence of singularity became one of the arguments for the non-minimal extension of the Einstein-Maxwell theory.…”
Section: Discussionmentioning
confidence: 99%
“…In the papers [9,13] we attracted a special attention to the solution (17)- (20) with regular metric. In particular, it was shown that, when q 1 = −q, q 2 = 4q, q 3 = −6q and q is positive, there are no horizons if the mass of the monopole is less than some critical mass M (crit) .…”
Section: Conditions For the Absence Of Naked Singularitymentioning
confidence: 99%
“…The problem of absence of the central spacetime singularity in the spherically symmetric objects has been raised by Bardeen in [10], and during next fifty years this problem has been studied in many aspects (see, e.g., [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]); mostly, the nonlinear electromagnetic field was considered as the guarantor of the regularity. Nonminimal coupling of the gauge and electromagnetic fields to the spacetime curvature, as a cause of regularity, was discussed in the papers [28][29][30][31][32][33]. In other words, there are at least two theories: first, the nonlinear electrodynamics, second, the nonminimal field theory, in the framework of which one can provide the regularity of the gravitational field at the center of the magnetic monopoles.…”
Section: Introductionmentioning
confidence: 99%
“…54, a three-parameter gauge-invariant nonminimal EYM model linear in curvature is considered. [55][56][57][58] Our goal is to formulate a nonminimal Einstein-Yang-Mills-Higgs (EYMH) theory, and this process, of course, also admits different approaches. In fact, the nonminimal EYMH theory should accumulate the ideas and methods from both the nonminimally extended EYM theory and the nonminimally extended scalar field theory.…”
Section: Introductionmentioning
confidence: 99%